Preliminary results of the use of combined diagnosis in malignant breast pathology - Laviña, Raúl; Mate, Miguel; Pressa, Carlos; Giossa, Walter; Falconi, Luis; Albo, Manuel; Arbes, Isabelino; del Campo, Alberto (Cirugía del Uruguay, 1984)
The work group of the Mammary Diagnostic Center of the Asociación Española 1 ° de S.M. with two years experience and 1.200 cases studied make ana eva• luation of the results of the Combined Diagnosis application, in a series of 43 breast cancers studied and treated.